CD27 on IgD-CD38-B Cells Mediates the Coprococcus-COPD Link - Gao Y; Chen L; Zhang J; Wen Z (International Journal of COPD)
Yaning Gao, Liang Chen, Jianhong Zhang, Zhengjun Wen Respiratory and Critical Care Medicine Department, Beijing Jingmei Group General Hospital, Beijing, People’s Republic of ChinaCorrespondence: Yaning Gao, Email 747808201@qq.comBackground: The gut-lung axis, representing the communication between gut microbiota and the lungs, has been hypothesized to influence chronic obstructive pulmonary disease (COPD) development through modulation of the immune response. However, the causal role of gut microbiota in COPD and the potential mediating role of immune cells remain largely undetermined. This study aimed to uncover the causal relationship between gut microbiota and COPD and explore the potential mediating role of immune cells in this connection.Methods: This study employed a two-step Mendelian randomization (MR) analysis to investigate the causal effect of gut microbiota on COPD and explore the potential mediating role of immune cells in this relationship. The inverse variance weighted method served as the primary MR analysis method.Results: MR analyses revealed statistically significant genetic associations between 28 gut microbiota and COPD. Among these, the genus Coprococcus demonstrated the strongest causal effect on COPD risk, exhibiting a significant positive association (odds ratio (OR) = 1.18, 95% confidence interval (CI): 1.03– 1.36, P = 0.03). Additionally, 15 immune cell traits displayed significant associations with Coprococcus. Notably, CD27 expressed on IgD− CD38− B cells emerged as a potential contributor to COPD development (OR = 1.04, 95% CI: 1.00– 1.07, P = 0.03). We further explored the potential mediating effect of CD27 on IgD− CD38− B cells in the relationship between Coprococcus and COPD.Conclusion: Our MR analysis provided evidence for a causal association between gut microbiota and COPD, potentially mediated by immune cells.Plain Language Summary: This study aimed to investigate whether gut bacteria could cause chronic obstructive pulmonary disease (COPD) and the potential role of immune cells in this process. We delved into the genetic associations between gut microbiota and COPD by employing Mendelian randomization analysis. The findings revealed a significant link between the genus Coprococcus and an increased risk of COPD. Additionally, the study identified 15 immune cell traits significantly associated with Coprococcus, among which CD27 expressed on IgD-CD38-B cells emerged as a potential key factor in COPD development. This study provides evidence for a causal relationship between gut microbiota and COPD, and suggests that immune cells may play a potential mediating role in this relationship.Keywords: chronic obstructive pulmonary disease, gut microbiota, immune cells, Mendelian randomization, gut-lung axis